y=x^3-x^2-1

y=x^2+15x-1

i completely forgot how to do this. i know method of elimination, but it says i gotta use substitution. any ideas?

Printable View

- Apr 1st 2009, 04:44 AMrobdarftwMethod of Substitution
y=x^3-x^2-1

y=x^2+15x-1

i completely forgot how to do this. i know method of elimination, but it says i gotta use substitution. any ideas? - Apr 1st 2009, 07:47 AMred_dog
Substitute y from the first equation in the second equation:

$\displaystyle x^3-x^2-1=x^2+15x-1\Rightarrow x^3-2x^2-15x=0\Rightarrow x(x^2-2x-15)=0$

Then $\displaystyle x=0$ or $\displaystyle x^2-2x-15=0$

Now solve the quadratic, then replace x and find y.